2017
DOI: 10.1093/cercor/bhx165
|View full text |Cite
|
Sign up to set email alerts
|

Autism Related Neuroligin-4 Knockout Impairs Intracortical Processing but not Sensory Inputs in Mouse Barrel Cortex

Abstract: Neuroligin-4 (Nlgn4) is a cell adhesion protein that regulates synapse organization and function. Mutations in human NLGN4 are among the causes of autism spectrum disorders. In mouse, Nlgn4 knockout (KO) perturbs GABAergic synaptic transmission and oscillatory activity in hippocampus, and causes social interaction deficits. The complex profile of cellular and circuit changes that are caused by Nlgn4-KO is still only partly understood. Using Nlgn4-KO mice, we found that Nlgn4-KO increases the power in the alpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 63 publications
5
27
4
Order By: Relevance
“…Reductions in synaptic signal-to-noise in cortical and hippocampal pyramidal neurons, driven by a change in the ratio of dendritic excitatory and inhibitory synapses, are widely thought to contribute to reduced efficiency of signal processing in ASD, a mechanism known as the E/I ratio hypothesis (67). We confirm E/I imbalance characterized by increased GABAergic activity and lower glutamatergic activity in CA3 neurons in Magel2 KO mice, consistent with observations made in other ASD models (68)(69)(70)(71). Furthermore, we report that perinatal OT administration restored normal GABAergic activity in Magerl2 KO mice without improving glutamatergic transmission.…”
Section: The E/i Ratio and Social Behaviorsupporting
confidence: 90%
“…Reductions in synaptic signal-to-noise in cortical and hippocampal pyramidal neurons, driven by a change in the ratio of dendritic excitatory and inhibitory synapses, are widely thought to contribute to reduced efficiency of signal processing in ASD, a mechanism known as the E/I ratio hypothesis (67). We confirm E/I imbalance characterized by increased GABAergic activity and lower glutamatergic activity in CA3 neurons in Magel2 KO mice, consistent with observations made in other ASD models (68)(69)(70)(71). Furthermore, we report that perinatal OT administration restored normal GABAergic activity in Magerl2 KO mice without improving glutamatergic transmission.…”
Section: The E/i Ratio and Social Behaviorsupporting
confidence: 90%
“…There is no clear correspondence with the phenotypes from these genes with those of our patient. The NLGN4 gene, for example, has been associated with manifestations within the autism spectrum, [39][40][41][42] which is not observed in our patient. On the other hand, our patient presents short stature but SHOX 42 , a known gene related to short stature, 43,44 that maps to the short arm of the X-chromosome, is not deleted in our patient.…”
Section: Discussioncontrasting
confidence: 52%
“…The same group demonstrated that expression of an ASD-related mutation of the postsynaptic adhesion molecule neuroligin-3 leads to an enhanced frequency of GDPs in the immature hippocampus (Pizzarelli and Cherubini, 2013 ). Knockout of neuroligin-4, another ASD related member of the neuroligin family, enhances the occurrence and duration of spontaneous spindle bursts in mouse cortex (Unichenko et al, 2017 ). In summary, these studies illustrate that an adequate amount of spontaneous activity may be the prerequisite for proper neurodevelopment, and both enhanced and reduced activity levels may lead to adverse outcomes.…”
Section: Pathophysiological Implications Of Disturbed Perinatal Neuromentioning
confidence: 99%